Molecular and mycotoxin characterization of Fusarium graminearum isolates obtained from wheat at a single field in Argentina - Ortega, Leonel Maximilano (2016)
Fusarium graminearum is the primary causal agent of Fusarium head blight of wheat in Argentina. This disease affects yield losses and quality of grains, reducing the wheat end-use, also causing mycotoxin contamination. In this study, the genetic variability and deoxynivalenol (DON) potential/production of F. graminearum sensu stricto (s.s.) isolates obtained from wheat samples of the 2009, 2010, and 2011 growing seasons from a single location in Argentina were evaluated. The genetic variability detected using inter-simple sequence repeat (ISSR) was analyzed in relation to the in vitro deoxynivalenol production, the main monitored and quantified mycotoxin according to the current regulations for the international marketing of cereals. Of the 68 F. graminearum s.s. isolates obtained in this study, 95 % showed a different banding pattern with ISSR molecular markers and a high variability was detected within the population. However, no clustering was found in relation with year or DON production. All isolates amplify for the DON-related gene and a high variability in DON production was observed among the isolates, with production values between non-producers and 1741 μg/g. The results suggest that the F. graminearum s.s. population varies significantly in both genetic structure and toxin production in a limited sampled area.